Drifting through landscapes: building on the tradition of the dérive through walking, drawing, and sensory experiences - Chen, Charling (Kansas State University, 2023)
As professionals who strive to design walkable, engaging, and evocative places, landscape architects can benefit from understanding how people physically and emotionally experience places. Yet, landscape architects often design from afar – from their office chairs and computer screens, using remote sensing technologies to access site imagery and data. Architect Juhani Pallasma argues that in our increasingly digital world, we prioritize visual perception over other sensory modes, which “flattens our magnificent, multi-sensory, simultaneous, and synchronic capacities of imagination by turning the design process into a passive visual manipulation, a retinal journey” (Pallasmaa 2005, 12). This study aims to ground site research in human experience through a multisensory lens. In addition to walking and visual perception, this study also investigates how sound, smell, and touch shape our sense of place. Based on the dérive, an exploratory walking method established by avant-garde artists in the 1950s (O’Rourke 2013), thirty-five student participants walked and explored various types of open spaces on a university campus. Participants were asked to take a twenty-minute walk within a four-week time frame. Each participant completed a trip diary, which included a short questionnaire, hand-drawn route map, sketch, and written descriptions of their sensory observations and emotional reactions. The collected data was synthesized and analyzed through a series of composite graphics and maps. Prominent themes that emerged from the data were grouped by sensory mode. Visual observations, captured through sketches and written descriptions, were categorized into the three facets of place – location, materiality, and meaning – as defined by humanistic geographers (Williams 2014). Emotional responses from the participants were plotted onto an adapted version of Russell’s (1998) circumplex model of emotion, revealing patterns between specific types of sensory experiences and emotions. Overall, elements of nature – such as wind, water, and trees – stimulated all the senses that were studied and evoked mostly pleasant emotions. These relationships occurred in the main quad, practice stadium, along a creek, and in small, more intimate gardens or pathways. In contrast, mechanical and industrial sounds and smells – such as traffic or utilities – triggered unpleasant emotions. These relationships consistently aligned with streets, main corridors, and next to buildings and infrastructure, such as the parking garage or power plant. Mixed or neutral emotions occurred in more enclosed, intimate spaces and were often not linked to specific causes. This finding suggests that participants may have recognized an emotional reaction, but not the cause. Similarly, they may have observed a sensory experience, but not its effect. Only 30% of the documented sensory observations were linked to an emotion. Furthermore, participants mapped sensory observations in major places on the campus – a main plaza, pedestrian corridor, and open lawn – but documented few or no emotional reactions. The absence of emotional indicators suggests that participants did not leave with strong impressions of these spaces. This study contributes to the advancement of place research and environmental perception by bridging the two bodies of knowledge through unique methods of research. While most studies focus on one or two sensory modes, this study examines four out of the five main human senses. In doing so, the combined auditory and haptic experience produced by walking on different ground textures emerged from the data as a unique example of multimodal perception and sensory congruency. Furthermore, unlike many sensory studies that are conducted in research labs, this study was conducted in a real-world setting. Most importantly, this study not only documents the variety of sensory observations, but also studies their relationship to human emotions. For place and sensory research to be more meaningful and applicable to the design profession, studies need to reflect human experiences in real places (Spence 2020). Walking, drawing, and direct observation can lead to new discoveries and generate new knowledge. The site research and analysis methods developed from this study can be adapted for professional practice, community engagement, or design education curriculum. The nature of the research activities is open-ended and inviting to people of all backgrounds. Mapping the data reveals challenges and opportunities that are collectively identified and voiced by participants. Designers are uniquely positioned at the intersection of art and science, and have the skills to gather, synthesize, interpret, and graphically communicate both qualitative and quantitative information. Thus, the methods from this study can be incorporated into design education or professional practice to encourage designers to engage with the places they design for through both their minds and their bodies.
Keywords: Landscape architecture; Sense of place; Sensory and emotion mapping; Environmental perception; Sketching in situ; Embodied knowledge